2018
DOI: 10.1093/ejcts/ezy252
|View full text |Cite
|
Sign up to set email alerts
|

Procedural risk factors, incidence and timing of reintervention after treatment for native coarctation of the aorta in children: a population-based study†

Abstract: Reinterventions after surgery in neonates were relatively common. In older children, percutaneous treatment carried a higher risk of reinterventions, which were mainly related to residual coarctation after primary treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
2
4
0
1
Order By: Relevance
“…Tulzer et al reported that EEEA could be performed with low perioperative mortality and morbidity, with freedom from reintervention of 90.12% at 10 years. In our experience, an aortic arch reintervention occurred in 4.4% at a very long‐term follow‐up, which compares better to most recent reports . Despite HAA was found to be a significant risk factor for recoarctation, as elsewhere reported, in our experience, EEEA for patients with HAA was still effective, since its freedom from reintervention on aorta was significantly higher than EEA (Figure B).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Tulzer et al reported that EEEA could be performed with low perioperative mortality and morbidity, with freedom from reintervention of 90.12% at 10 years. In our experience, an aortic arch reintervention occurred in 4.4% at a very long‐term follow‐up, which compares better to most recent reports . Despite HAA was found to be a significant risk factor for recoarctation, as elsewhere reported, in our experience, EEEA for patients with HAA was still effective, since its freedom from reintervention on aorta was significantly higher than EEA (Figure B).…”
Section: Resultssupporting
confidence: 81%
“…B, When analyzing survival among the three classes of age, there was a significant difference between patients operated less than 1 month and the remaining (P = 0.0095); in particular, when comparing neonates with infants and children, P = 0.0172 and 0.0131, respectively reports. 13,[16][17][18] Despite HAA was found to be a significant risk factor for recoarctation, as elsewhere reported, 14 in our experience, EEEA for patients with HAA was still effective, since its freedom from reintervention on aorta was significantly higher than EEA ( Figure 3B).…”
Section: Commentsupporting
confidence: 79%
“…Surgical reinterventions were related to lower body weight and smaller aortic dimensions at the time of surgery. In the percutaneous group, higher residual gradients or planned repeat procedures were associated with reintervention [21]. These data suggest a benefit for surgery in smaller patients.…”
Section: Survival and Reinterventionmentioning
confidence: 72%
“…[9][10][11]21,24,25 İlk bir yaşta balon anjiyoplasti sonrası rekoarktasyon sıklığı %40, 1 yaş üstü çocuklarda %10-30 olarak bulunmuştur. 12,16,20,22,26,27 Rekoarktasyon oranlarımızın diğer çalışmalara göre daha yüksek olması, yaş gruplarının daha küçük çocuklardan meydana gelmesi ile açıklanabilir. Süt çocukluğu grubunda (4-12 ay) hastaların büyük çoğunluğunu (%85) 4-6 aylık çocuklar oluşturuyorken, yine aynı şekilde 1 yaş üzeri grupta, hastaların yarısını 13-36 aylık çocuklar oluşturmuştur.…”
Section: Discussionunclassified